2021
DOI: 10.3390/v13081643
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Phylogenetics in Unravelling Patterns of HIV Transmission towards Epidemic Control: The Quebec Experience (2002–2020)

Abstract: Phylogenetics has been advanced as a structural framework to infer evolving trends in the regional spread of HIV-1 and guide public health interventions. In Quebec, molecular network analyses tracked HIV transmission dynamics from 2002–2020 using MEGA10-Neighbour-joining, HIV-TRACE, and MicrobeTrace methodologies. Phylogenetics revealed three patterns of viral spread among Men having Sex with Men (MSM, n = 5024) and heterosexuals (HET, n = 1345) harbouring subtype B epidemics as well as B and non-B subtype epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…A study from the USA concluded that transmission during the first year of infection was partially linked to high viral load ( Little et al., 2014 ). Similarly, a more recent study from Canada showed that cluster growth was related to transmission from early-stage infection, and this is likely due to HIV strains being more transmissible during this initial period of the infection ( Brenner et al., 2021 ). Thus, early diagnosis and early initiation of ART to reduce viral load is key for reducing transmission rates.…”
Section: Molecular Epidemiology For Guiding Hiv Public Health Interve...mentioning
confidence: 97%
“…A study from the USA concluded that transmission during the first year of infection was partially linked to high viral load ( Little et al., 2014 ). Similarly, a more recent study from Canada showed that cluster growth was related to transmission from early-stage infection, and this is likely due to HIV strains being more transmissible during this initial period of the infection ( Brenner et al., 2021 ). Thus, early diagnosis and early initiation of ART to reduce viral load is key for reducing transmission rates.…”
Section: Molecular Epidemiology For Guiding Hiv Public Health Interve...mentioning
confidence: 97%
“…Because real epidemics typically feature super-spreading and because this can have a large influence on genetic diversity of a pathogen [ 16 ], the population was further stratified into two risk categories with 20% of individuals assigned to a high-risk group, associated with a 10-fold higher rate of HIV transmissions compared to the individuals in the low-risk group [ 15 ].…”
Section: Network Simulationsmentioning
confidence: 99%
“…Surveillance should include advance sequencing methods to detect the variations which could implicate enhanced zoonotic potential or pathogenicity [ 39 ]. There are many examples how these modern methods coupled with classical epidemiology result in the better understanding of infectious disease transmission, and in some cases, better outcomes [ 40 ].…”
Section: Preventing the Next Pandemicmentioning
confidence: 99%